Evaluation of rice (Oryza sativa) and legume intercropping in upland situation of Bihar plateau - BANIK, P; BAGCHI, D K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1989-90 and 1990-91 to assess the advantages or disadvantages of rice (Oryza sativa L.) + legume intercropping system on sandy upland loamy soil in Bihar plateau, Rice, soybean [Glycine max (L.) Merr.], blackgram (Phaseolous mungo L.), greengram (P. radialus L.) and pigeonpea [Cajanus cajan (L.)Millsp.] were sown in sole and 2: 1 intercrop combination. Rice +pigeonpea was the best system, followed by rice + soybean with rice-equivalent yield of 2.665 and 2.478 tonnes/ha compared with 2.254 tonnes/ha from rice alone. Pigeonpea and soybean were better-suited crops than rice for this type of soil. Competition ratio indicated rice as the dominated eomponent in combination with pigeonpea, but with blackgram and greengram both the components were nearly equally competitive. Soil-nitrogen enrichment through legume cultivation contributed to higher yield of the succeeding indian mustard [Brassica juncea (L.) Czemj. & Cosson] crop.